The study on the integration of Activity Based Costing (ABC) system and six-sigma principle - Wan Hamid, Wan Harun; Mohd. Rohani, Jafri (Universiti Teknologi Malaysia, 2005)
Manufacturing organizations are facing much more challenges as compared to the earlier years. The important and crucial decisions have to be taken by the management in continuous basis in order to ensure the survival and competitiveness of company throughout the journey to become a successful organization. In order to make these decisions fast and correct, they need more accurate information related to financial and non-financial aspects. The conventional cost management systems, which were developed decades ago are unable to provide all information required to make right decision, justify the cost reduction and process improvements (Chen, 1996). This is because they were based on labor-intensive production system while today’s production processes are more sophisticated and faces constant changes. An alternative costing system, Activity Based Costing (ABC) has emerged to the new solution to costing system. It provides financial and non-financial information not only for product costing but also for each activity of manufacturing process. It can list and measure the cost of each activity individually in production and in supporting activities to deliver of a product or service right to customers (Sohal & Chung, 1998). ABC focuses on the activities performed to produce the products throughout the manufacturing process (Gunasekaran et al., 1999). By assigning other costs, such as marketing and administrative to cost object, ABC able to provide more accurate product costs. It helps to improve the operational performance by allocating overhead costs correctly. It provides cost information based on the actual consumption of the resources by each particular activity. The goal of ABC is to reveal cost allocation information by tracing the production costs accurately to activities and product (Gunasekaran et al., 1999). The implementation of ABC has provided many benefits, such as more accurate product costing, providing of cost behavior information and tracing resources consumptions. Realizing many benefits gain from implementation of ABC, many companies have embarked in applying ABC system. However, there are many problems and barriers they encountered during the implementation, which made some has decided to abort this system and not be able to exploit its advantages. It is the objective of this study to help foster the growth of Malaysian companies by helping them to provide better understanding,knowledge and skills to take advantage of using ABC as a tool to improve their manufacturing process. The title of the project is The Study on Integration of Activity-based Costing and Six-sigma Principle. The specific objective of the study is to determine success factors for ABC implementation in manufacturing companies based on Six-sigma process improvement principle. The focus of the study is to identify and understand the critical success factors in implementation of ABC, to identify and specified the problems and barriers and to understand their relationship with the ABC success. In order to identify, understand and formulate the proposed solution, this study will use a survey approach to get required data for further analysis. The survey will be based on mailed questionnaires to selected manufacturing industries in Malaysia. In order to formulate a comprehensive and relevant set of questionnaires, a comprehensive review of literature will be studied, followed by validation and verification process,which involved expert opinions and a pilot study. The next phase is where data from the study will be analyzed to identify areas related to the level of acceptance of ABC,the critical success factors and also to determine the relationship between the organization’s factors and the success of implementation of ABC system. The tangible outcome of this project is to provide a set of proposed guidelines and support tools for manufacturing organizations in applying Activity-based Costing for process improvement efforts as suggested by Six-sigma improvement principle.